Expatriação e repatriação de profissionais brasileiros: desafios pessoais, profissionais e familiares - Souza, José Felipe Ferreira de (2015)
The expatriation is one of the main strategies used by internationalized companies to manage their international practices and ensure better communication between the mother company and their subsidiaries. From an organizational point of view there are several reasons to a company send a expatriate and these reasons, many times, don t dialogues with the reasons that do the professional accepts the international mission. By accepting to be expatriate, the professional usually create high expectations about the return, imagining the professional growth, increases in benefits and salary and best positions in the company. During the process of expatriation and repatriation, many obstacles are overcome, such as intercultural adjustment in the going and return. The literature suggests that if there is no intercultural adjustment the expatriate will be unable to perform their functions and the international mission will fail, negatively affecting the company and the professional. To deal with cultural impact and ensure proper intercultural adjustment, the company needs to assist the professional from the initial stages of expatriation, while still in the origin country, with intercultural training, until the repatriation of the professional, with supports to help to deal with the reverse cultural impact. From this contexto, this research seek, through the perspective of Brazilian expatriates and repatriates, capture the opinions of the professionals about how was the process of expatriation and repatriation. For that, three stages were defined: (1) understand the phenomenon of internationalization of companies, (2) define the expatriation and repatriation processes and (3) develop a survey with professional expatriates and repatriates. This research used an exploratory-descriptive and qualitative methodology. The focus of the discussion was talk with the professionals to capture their views about the process of expatriation and repatriation. The results signaled that when intercultural adjustment is neglected by the company hardly the international mission has successfully. Also was observed that the motivations that lead professionals to accept the expatriation are determinants to the success of expatriation